2020
DOI: 10.1097/md.0000000000019104
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic stability during adrenalectomy for pheochromocytoma

Abstract: Hemodynamic stability is one of the most critical aspects of adrenal surgery for pheochromocytoma. Few articles have evaluated the hemodynamic status of patients undergoing posterior retroperitoneal adrenalectomy (PRA) for pheochromocytoma. The aim of this study is to compare the intraoperative hemodynamic parameters between lateral transperitoneal adrenalectomy (TPA) and PRA in this groups of patients. This report describes a retrospective study of 53 pheochromocytoma patients who underwent endosc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 30 publications
0
24
0
Order By: Relevance
“…Among the seven studies on the EBL (11)(12)(13)(14)(15)(16)19), obvious heterogeneity was observed, so we applied random effect model to statistical analysis. Our final outcomes indicated statistically significant difference between PRA and LTA (MD: −15.17; 95% CI, −26.63 to −3.72; P = 0.009, Figure 2B).…”
Section: Estimated Blood Lossmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the seven studies on the EBL (11)(12)(13)(14)(15)(16)19), obvious heterogeneity was observed, so we applied random effect model to statistical analysis. Our final outcomes indicated statistically significant difference between PRA and LTA (MD: −15.17; 95% CI, −26.63 to −3.72; P = 0.009, Figure 2B).…”
Section: Estimated Blood Lossmentioning
confidence: 99%
“…The conversion rate was recorded in seven of nine researches (11)(12)(13)(14)(15)(16)(17). Since the heterogeneity test outcome (I 2 = 0%), we used fixed effects model.…”
Section: Conversion Ratementioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have compared the surgical outcomes of LTA and PRA. These reports demonstrated clinically equivalent outcomes, with a smaller tumor size, less estimated blood loss (EBL), a shorter time to oral intake, and a shorter length of hospital stay in the PRA group ( Table 1 ) [ 19 , 21 28 ]. A recent meta-analysis reported significant differences in demographic characteristics and surgical outcomes between LTA and PRA groups.…”
Section: Comparison Of Surgical Outcomes Between Lta and Pramentioning
confidence: 99%
“…Therefore, the treatment of smaller tumors is more likely to be successful with this posterior approach. Several studies have reported that tumors smaller than 8 cm could be safely removed by the PRA technique, so larger tumors (with a size exceeding approximately 8 cm) are more usually removed by LTA [ 21 ]. Because of selection bias, tumor size might have played a role as a confounding factor regarding the tendency for a shorter operation time, less EBL, a shorter time to oral intake, and a shorter length of hospital stay in PRA.…”
Section: Comparison Of Surgical Outcomes Between Lta and Pramentioning
confidence: 99%